Effectiveness of Goat Manure and Liquid Organic Fertilizer in Increasing The Growth and Production of Cucumber (Cucumis sativus L.) - Safrizal, Safrizal; Ginting, Ina Febria; Arinda, Dela; Mei Ryan Sandi (Universitas Medan Area, 2024)
This study aims to analyze the effect of goat manure and liquid organic fertilizer on the growth and yield of cucumber plants. This research was conducted in the Experimental Garden of the Faculty of Agriculture, Syiah Kuala University using a Randomized Group Design (RAK) factorial pattern with two factors: the dose of goat manure consists of 4 levels, namely: K0: Without goat manure (0 ton/ha), K1: 10 tons/ha, K2: 20 tons/ha, K3: 30 tons/ha. The liquid organic fertilizer factor consists of 4 levels, namely P0: Without liquid organic fertilizer (0 ml/liter of water), P1: 5 ml/liter of water, P2: 10 ml/liter of water, and P3: 15 ml/liter of water. The parameters observed consisted of plant height, fruit number, fruit diameter, fruit length, and fruit weight. The results showed that the application of goat manure had a significant effect on plant height (15, 30, and 45 HST) and fruit length, but had no significant effect on fruit diameter, fruit number, and fruit weight. In contrast, the application of liquid organic fertilizer, either singly or in interaction with goat manure, showed no significant effect on all parameters observed. This study concludes that goat manure is effective in increasing plant growth.